Whole-Genome Sequence Analysis, Probiotic Potential, and Safety Assessment of the Marine Bacterium Paraliobacillus zengyii CGMCC1.16464 - Qianjin Fan; Mengqi Jiao; Haoyue Huangfu; Lan Chen; Beijie Li; Zhijie Cao; Xuelian Luo; Jianguo Xu (Marine Drugs)
Paraliobacillus zengyii CGMCC1.16464 (P. zengyii) is a novel antiviral probiotic candidate strain. To ensure its safety as a potential probiotic, a safety evaluation was conducted in this study. The safety and functional potential of P. zengyii were systematically assessed through genomic bioinformatics analysis, in vitro experiments, and acute oral toxicity tests in mice. Genomic analysis revealed that P. zengyii is rich in genes related to carbohydrate and amino acid metabolisms and carries genes encoding antimicrobial and antiviral agents (such as ectoine, type III polyketide synthase, and lasso peptides). It also expresses gastrointestinal tolerance-related proteins (ClpC, GroEL, and ClpP). Its resistance to polymyxins is an inherent trait with no risk of plasmid-mediated transfer. In vitro experiments confirmed that P. zengyii is somewhat tolerant to bile salts and acidic environments and does not exhibit hemolytic or gelatinase activity. Importantly, an acute oral toxicity test in mice revealed that after intervention with high, medium, or low doses, no significant abnormalities in the body weight, organ index, or tissue morphology of the mice were observed. In conclusion, P. zengyii exhibited good safety and probiotic potential in terms of genomic safety, metabolic function, and in vitro and in vivo toxicities, providing a theoretical basis for the development of novel functional probiotics.